Association of Recent and Long-Term Supplement Intakes With Laboratory Indices in Patients With COVID-19 in Tehran, Iran, During 2020 - Hashemi, Rezvan; Montazer, Mohsen; Salehi, Zahra; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Background: Although previous studies observed the relationship between individual dietary supplements and enhancing body resistance against viruses, few studies have been conducted regarding the role of different supplements in treatment of COVID-19. The present article aimed to determine the association of recent and long-term supplements consumption on the biochemical indices and impatient duration among patients with COVID-19. Methods: In this cross-sectional study on 300 adult men and women with COVID-19, recent and long-term supplement intakes were investigated by using a questionnaire. In addition, lifestyle was also assessed in aspects of fruits and vegetable consumption, physical activity, sleeping duration, fluid intake, as well as smoking status. Furthermore, the laboratory and paraclinical parameters were obtained from medical records. The relationship between supplements intake with the length of hospitalization as well as clinical laboratory tests was investigated by one-way analysis of variance (ANOVA). Results: Those patients with supplements intake in the last 2 months had a significantly lower amount of blood urea nitrogen (BUN) (31.31 ± 13.87 vs 37.57± 19.77 mg/dL, P: 0.002) and higher serum 25(OH)D (28.13 ± 14.09 vs 23.81± 13.55 ng/mL, P: 0.03). Subjects with long-term supplement intake had a significantly lower invasive oxygen support (0.00 vs 5.10 %, P: 0.05), lactate dehydrogenase (LDH) (498.11 ± 221.43 vs 576.21±239.84 U/L, P: 0.02), fewer days of fever (0.49 ± 3.54 vs 2.64 ± 9.21, P: 0.02) and higher serum 25(OH)D (31.03 ± 13.20 vs 22.29± 13.42 ng/mL, P< 0.001). The length of hospital stay was practically the same between groups who received and did not receive supplementation during the 2 months prior to hospitalization. (6.36 ± 3.32 vs. 6.71± 4.33 days, P: 0.004). Similarly, people who took supplements during the past year had practically similar hospitalization lengths (6.29 ± 4.13 vs. 6.74± 3.55 days, P: 0.004). Conclusions: In conclusion, although practically the length of hospital stay was the same in both groups of supplements consumers and others, immune-boosting supplements were associated with improved several laboratory indices. However, due to the cross-sectional nature of our study, further longitudinal studies seem to be essential.